IMPROVING LANGUAGE TEACHING MATERIALS: STRATEGIES FOR EFFICIENT AND ENGAGING RESOURCES - Shakhnoza Ziyakulova (Journals Park Publishing, 2024)
Effective language instructional materials substantially impact student engagement and learning results. Uzbekistan's secondary education system has issues including obsolete resources, restricted technology, and inadequate cultural adaptation, which impede English language instruction. This article examines solutions to tackle these difficulties, emphasizing contextual relevance, gamification, multimedia integration, and cultural alignment. By integrating local cultural components, practical scenarios, and advanced technologies such as AI, VR, and AR, instructors may develop lessons that are interactive, engaging, and culturally pertinent. The article underscores the significance of integrating global viewpoints with local contexts to cultivate critical thinking, communication abilities, and cultural pride in learners. It offers a practical and theoretical foundation for the creation of educational materials that foster lifelong learning and equip students for global opportunities.
Keywords: Language teaching materials, Uzbekistan, cultural relevance, gamification, multimedia learning, technology integration, pedagogy, virtual reality, augmented reality, AI in education.